Effect of ECAP die angle on mechanical properties and biocompatibility of SS316L - Dayangku Noorfazidah, Awang Sh'ri; Zahiruddeen Salam, Zahari; Yamamoto, Akiko (MDPI AG, 2021)
In this study, ultrafine grain (UFG) SS316L was produced using an equal channel angular pressing (ECAP) process at two different die angles namely 120° and 126°. The effect of different die angles on mechanical, corrosion, and surface properties were thoroughly investigated. Furthermore, the subsequent effect on the cytotoxicity of SS316L was investigated. The microstructure observation shows ECAP processing has produced an elongated, finer grain size at 120° than 126°. The ECAP processing also increases the hardness of SS316L. There is no change in wettability and surface roughness observed. However, the ectrochemical measurement reveals that ECAP processing improves the corrosion resistance of SS316L. The cytocompatibility of ECAPed SS316L was evaluated by both a direct and an extract methods, finding the contribution of grain refinement by ECAP processing.